Liver abnormalities in typhoid fever in children - Triwibowo Soedjas, Triwibowo Soedjas (Universitas Gadjah Mada, 1983)
Fifty two patients with typhoid fever were studied. Hematomegaly occurred in 7I % of the patients. Hepatic enlargement was noted in the first week as well as during the course of the disease but the maximum incidence was found in the second week. Almoimal liver function tests were found in both groups, with and without hepatomegaly. Jaundice was present in 2 cases.Biopsies showed focal necrosis, cellular infiltration. Kupffer cell proliferation and hydropic degeneration. Typhoid nodules were demonstrated in 2 out of the 7 cases.The prognosis of typhoid fever with liver abnormalities is good and requires no further treatment.Key Words: hepatomegaly - abnormal liver function test - jaundice - liver biopsy - nonspecific reactive hepatitis